Mid- and long-term (at least 12 months) follow-up of patients with spinal muscular atrophy (SMA) treated with nusinersen, onasemnogene abeparvovec, risdiplam or combination therapies: A systematic review of real-world study data. (July 2022) - Erdos, Judit; Wild, Claudia
Abstract: Objectives: This systematic review aimed to assess mid- and long-term (at least 12 months) real-world study data from all types of spinal muscular atrophy (SMA) patients treated with any of the approved drugs or combination therapies. Methods: A systematic literature search was carried out in five databases. Two authors selected the studies based on pre-defined selection criteria and independently graded the risk of bias at study level. Results: Five hundred forty-six records were identified in the literature search and 22 studies (in 26 publications) were included in the analysis. Nusinersen, onasemnogene abeparvovec and combination therapies improved motor endpoints in SMA type 1 patients. SMA type 2 to type 4 patients treated with nusinersen showed stabilisation or small improvements in motor endpoints with some deterioration observed. Quality of life endpoints, such as respiratory and nutritional support were poorly reported on. Drug-related adverse events occurred rarely in all types of SMA patients with all assessed drugs. Mid- and long-term studies on risdiplam could not be identified. Conclusions: The large quantity of missing data and heterogeneity of studies hinder comparability. Although stability and further improvement on the long-term is still uncertain, the results from the included evidence, as well as from pivotal trials show a striking contrast to the natural progression of the disease. Highlights: Mid- and long-term real-world study data on all types of SMA patients. Studies on nusinersen, onasemnogene abeparvovec and combination therapies included. Mortality, discontinuation of therapy, motor endpoints, and safety endpoints analysed.